Design and development of skin detection model based deep learning on different skin tones - Al-Qaysi, Mohammed Ahmed Chyad (Tanjong Malim, 2021)
Design and development of skin detection model based deep learning on different skin tones by Al-Qaysi, Mohammed Ahmed Chyad